2017
DOI: 10.1515/acph-2017-0008
|View full text |Cite
|
Sign up to set email alerts
|

Public health care system, a quasi-experimental study: Acceptance and attitude to implicate clinical services

Abstract: A six-month longitudinal intervention arm study with a pre-post cross-sectional questionnaire-based survey was performed. A 3-phase objective structured clinical examination (OSCE) design was utilized for evaluation of acceptance and attitude of pharmacy students towards clinical pharmacy services. The pre-OSCE survey showed increased disagreement with the role of clinical pharmacists, compared to a significant positive shift in attitude towards their services in the healthcare team after 6 months of the trial… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

0
7
0
2

Year Published

2018
2018
2024
2024

Publication Types

Select...
6

Relationship

3
3

Authors

Journals

citations
Cited by 10 publications
(9 citation statements)
references
References 20 publications
(16 reference statements)
0
7
0
2
Order By: Relevance
“… 3 , 6 However, several studies reported a strong influence of patient-related factors on blood glucose intolerance, including perception and self-care behavior. 3 , 6 , 8 , 11 Self-care, including self-monitoring of blood glucose, showed a positive effect on controlled glycemic levels, 4 , 7 , 9 , 10 , 11 considering the fact that diabetes-related disease knowledge plays a vital role in association with self-care behaviors of a patient. 12 In addition, the long-term adverse effects of the disease reduce the self-care behaviors of patients and result in poor health state and HRQoL.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“… 3 , 6 However, several studies reported a strong influence of patient-related factors on blood glucose intolerance, including perception and self-care behavior. 3 , 6 , 8 , 11 Self-care, including self-monitoring of blood glucose, showed a positive effect on controlled glycemic levels, 4 , 7 , 9 , 10 , 11 considering the fact that diabetes-related disease knowledge plays a vital role in association with self-care behaviors of a patient. 12 In addition, the long-term adverse effects of the disease reduce the self-care behaviors of patients and result in poor health state and HRQoL.…”
Section: Introductionmentioning
confidence: 99%
“… 15 None of the studies have discussed these factors among Malaysian populations. Malaysia is a multiethnic society with different lifestyle patterns and religious practices, 2 , 3 , 8 , 9 mainly consisting of Malay, Chinese, and Indian ethnicity. In this diverse population, it is essential to determine the HRQoL multiconstruct model.…”
Section: Introductionmentioning
confidence: 99%
“…Therefore, T2DM is considered as a major threat to public health [ 5 ]. Early incidence of T2DM in adults increased the risks of both micro and macrovascular complications which in term lead to poor health-related quality of life [ 6 8 ].…”
Section: Introductionmentioning
confidence: 99%
“…Diabetes management focus on multifactorial concept, several demographic, clinical as well as behavioral factors influence the patient-specific disease outcomes [ 7 , 10 ]. Glycemic control is one of the ultimate tools to evaluate the patient’s disease progression and treatment success [ 3 , 6 ] however, clinical literature showed that not only treatment but patient’s perception and self-care behavior are also strong mediating factors for glycemic control among T2DM patients [ 3 , 6 , 8 , 11 ]. Several studies have shown positive effect of self-care management to glycemic index [ 4 , 7 , 9 11 ], also diabetic-related knowledge is considered as an important factor for development/improvement in self-care behavior and practices [ 12 ].…”
Section: Introductionmentioning
confidence: 99%
“…Self-care is the one of the important factor for achieving optimal glycemic levels among patients with IDDM [ 2 , 3 ]. Diabetes patients are responsible for their daily care, such as self-monitoring blood glucose (SMBG), diet management, and insulin dose adjustments [ 5 , 6 ]. Diabetes affects the daily life functioning therefore, lowering the health status and QOL among patients [ 1 , 2 ].…”
Section: Introductionmentioning
confidence: 99%